Rayon-based activated carbon fabric with controlled porosity: advanced barrier against chemical warfare agents (CWAs) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
Currently, activated carbon fibre (ACF) is a material of choice for various adsorption applications, offering numerous advantages over conventional forms of activated carbon, such as powders and beads. Among the possible precursors for ACF-like pitch, PAN, and phenol, rayon is relatively cheaper and abundantly commercially available. We report here the preparation of ACF from a commercially available rayon-based carbon fabric via gasification in a CO2 atmosphere. A series of four samples was prepared by varying activation time (4 h, 4.5 h, and 5 h) and temperature (850 °C, 900 °C & 950 ℃) at a constant CO2 flow rate of 100 ml/min. The prepared ACFs were assessed for Brunauer-Emmett-Teller (BET) surface area, distribution of pores, and adsorption isotherms. Further, activated carbon was investigated using X-ray diffraction and field-emission scanning electron microscopy. The chemical environment of the carbonized & ACF samples has been assessed through FTIR. The evaluation of fabric properties in terms of mass, bending length, and flexural rigidity for carbonized fabric and ACF was also carried out. The prepared ACFs show a well-developed porous structure and activated carbon in a self-supporting textile form. The optimum activation conditions were obtained for ACF prepared at 900 ℃ for an activation duration of 4 h in CO2 with a flow rate of 100 ml/min. The material is predominantly microporous and suitable for the adsorption of hazardous chemicals. The prepared ACF may find many usages in different adsorptional applications for the removal of toxic gases and as an adsorbent medium against lethal chemical warfare agents in military clothing systems.